Objects, Components, Models and Patterns 47th International Conference, TOOLS EUROPE 2009, Zurich, Switzerland, June 29-July 3, 2009. Proceedings - Oriol, Manuel; Meyer, Bertrand; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This book constitutes the thoroughly refereed proceedings of the 47th International Conference on Objects, Components, Models and Patterns, TOOLS EUROPE 2009, held in Zurich, Switzerland, in June/July 2009. TOOLS has played a major role in the spread of object-oriented and component technologies. It has now broadened its scope beyond the original topics of object technology and component-based development to encompass all modern, practical approaches to software development. At the same time, TOOLS has kept its traditional spirit of technical excellence, its acclaimed focus on practicality, its well-proven combination of theory and applications, and its reliance on the best experts from academia and industry. The 17 regular papers and two short papers presented in this book, together with two invited papers, were carefully reviewed and selected from 67 submissions. The topics covered in this volume are reflection and aspects, models, theory, components, monitoring, and systems generation.
Invited Presentations -- On Realizing a Framework for Self-tuning Mappings -- Programming Models for Concurrency and Real-Time -- Reflection and Aspects -- CIF: A Framework for Managing Integrity in Aspect-Oriented Composition -- A Diagrammatic Formalisation of MOF-Based Modelling Languages -- Designing Design Constraints in the UML Using Join Point Designation Diagrams -- Stream-Based Dynamic Compilation for Object-Oriented Languages -- Models -- Algebraic Semantics of OCL-Constrained Metamodel Specifications -- Specifying and Composing Concerns Expressed in Domain-Specific Modeling Languages -- Early Crosscutting Metrics as Predictors of Software Instability -- Extensibility in Model-Based Business Process Engines -- Theory -- Guaranteeing Syntactic Correctness for All Product Line Variants: A Language-Independent Approach -- A Sound and Complete Program Logic for Eiffel -- Components -- A Coding Framework for Functional Adaptation of Coarse-Grained Components in Extensible EJB Servers -- A Leasing Model to Deal with Partial Failures in Mobile Ad Hoc Networks -- Monitoring -- Reusing and Composing Tests with Traits -- Flow-Centric, Back-in-Time Debugging -- A Classification Framework for Pointcut Languages in Runtime Monitoring -- Systems Generation -- Fast Simulation Techniques for Design Space Exploration -- PyGirl: Generating Whole-System VMs from High-Level Prototypes Using PyPy -- Short Papers -- Using Grammarware Languages to Define Operational Semantics of Modelled Languages -- Automatic Generation of Integrated Formal Models Corresponding to UML System Models.
Keywords: Computer science; Software engineering; Computers; Management information systems; Computer Science; Software Engineering/Programming and Operating Systems; Software Engineering; Models and Principles; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems; Electronic books